Decolorization of Sapindus Pericarp Extract by Hydrogen Peroxide and a Comparison of Basic Characteristics Before and After Decolorization. Issue 5 (20th March 2014) - Wang, Na; Wang, Heya; Weng, Zhen; Zhang, Cui; Wu, Heng; Guo, Youzhi; Sun, Zhiyong; Yao, Weirong
Abstract: The saponins from the pericarps of Sapindus mukorossi Gaertn. (Sapindaceae) are attracting more and more attention because of their antimicrobial activity and their ability to act as a natural surfactant. However, the color of Sapindus pericarp extract is dark brown, which limits its application in some products. The present study aims to improve the color by adding hydrogen peroxide. An orthogonal L9 (3) 4 test design was applied to optimize the decolorization parameters, including the amount of added hydrogen peroxide, time, temperature and pH. The extent of decolorization was up to 89.5 % below 80 °C within 80 min, using 2.5 % hydrogen peroxide at pH 6. The characteristics of Sapindus pericarp extract before and after bleaching were compared, including the antimicrobial and foaming performance, surface activities and detergency properties. There was no significant difference in either the diameters of the inhibition zone or the minimum inhibitory concentration against Candida albicans, Trichophyton rubrum and Pseudomonas aeruginosa ( P < 0.05), while these parameters for C. albicans, T. rubrum and P. aeruginosa for the sample after decolorization were 22.33, 25.00, 15.33 mm and 0.91, 0.91, 13.03 mg/mL, respectively. The foamability of the Sapindus pericarp extract after decolorization was somewhat enhanced and the foam stability reduced ( P < 0.05). There were no significant differences in values of the critical micelle concentration of the pericarp extract before and after decolorization. The detergency also remained at the same level. Our results show that the properties of the decolorized Sapindus pericarp extract were largely unchanged. This suggests that further development is worthwhile.